Proteomics analysis reveals the mechanism associated with changes in fatty acids and volatile compounds of brown rice infested by Sitophilus oryzae Motschulsky. (January 2022) - Hao, Jiarong; Tian, Xuemei; Wu, Fenghua; Hu, Hao; Zhou, Guoxin; Liu, Xingquan; Zhang, Tao
Abstract: The infestation of Sitophilus oryzae Motschulsky has been regarded as the most common problem in the storage of brown rice. Volatile compounds and fatty acids were investigated by gas chromatography–mass spectrometry, and the mechanism was studied using proteomics to evaluate the effect of S. oryzae on fatty acids and volatile compounds in brown rice. In this study, infestation reduced the contents of fatty acids, such as palmitic (C16:0) and stearic (C18:0) acids. A total of 27 differential volatile compounds were identified by partial least square-discrimination analysis, and six of these compounds might be due to fatty acid oxidation after the infestation of brown rice. Proteomics technology was applied to determine the mechanisms. A total of 105 proteins with significant changes (fold change (FC) > 1.20 or < 0.83, P  < 0.05) were determined in brown rice. The acyl carrier protein of the fatty acid synthesis was significantly downregulated in infested brown rice, which could explain the changes in fatty acids and volatile compounds. This study provides a proteomic insight into storage pest infestation in brown rice and is expected to be beneficial for controlling storage pests. Graphical abstract: Image 1 Highlights: Infestation decreases the contents of fatty acids. Six of differential volatile compounds were considered to be due to fatty acid oxidation after the infestation of brown rice. The changes in fatty acids and volatile compounds were caused by the accumulation of downregulation of acyl carrier proteins.